Kuhn and Feyerabend: For an humanistic, plural and open science - Navarro Fuentes, Carlos Alberto (2025)
We explore the revolutionary ideas of Thomas Kuhn and Paul Feyerabend in the context of the philosophy of science. Both challenged traditional conceptions of science, advocating for a more human, critical and pluralistic vision of the discipline and interrogating its epistemological, metaphysical and ontological foundations from a historiographic, sociological and cultural perspective, agreeing that science is a complex and human enterprise diverse that benefits from the plurality of approaches and openness to new perspectives, so only plural openness can contribute to a richer social understanding of scientific activity.